Strain Coupling of Conversion‐type Fe3O4 Thin Films for Lithium Ion Batteries. (29th May 2017) - Hwang, Sooyeon; Meng, Qingping; Chen, Ping‐Fan; Kisslinger, Kim; Cen, Jiajie; Orlov, Alexander; Zhu, Yimei; Stach, Eric A.; Chu, Ying‐Hao; Su, Dong
Abstract: Lithiation/delithiation induces significant stresses and strains into the electrodes for lithium ion batteries, which can severely degrade their cycling performance. Moreover, this electrochemically induced strain can interact with the local strain existing at solid–solid interfaces. It is not clear how this interaction affects the lithiation mechanism. The effect of this coupling on the lithiation kinetics in epitaxial Fe3 O4 thin film on a Nb‐doped SrTiO3 substrate is investigated. In situ and ex situ transmission electron microscopy (TEM) results show that the lithiation is suppressed by the compressive interfacial strain. At the interface between the film and substrate, the existence of Li x Fe3 O4 rock‐salt phase during lithiation consequently restrains the film from delamination. 2D phase‐field simulation verifies the effect of strain. This work provides critical insights of understanding the solid–solid interfaces of conversion‐type electrodes.